Optimasi Penggunaan Lahan Berdasarkan Kelas Kesesuaian Lahan untuk Pengembangan Tanaman Perkebunan (Studi Kasus: Kabupaten Sumba Timur Provinsi Nusa Tenggara Timur) - Marthen Makaborang; Sunarto Goenadi; Pramono Hadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
In order to study the suitability of land for development of cashew (Anacardium occidentale L), coffee var. robusta and vanilla crops and also to obtain maximum benefit. This research was conducted in District of Karera East Sumba sub- province. ArcGIS was used to assess land suitability by means overly of some maps such as: elevation, topography, soil type, soil texture, depth of land, clauses of farm for crop cashew, coffee var. robusta and vanilla to get the land suit ability class map. After obtaining map of land suitability, optimization was done using linear programming POMwin to obtain maximum benefit by applying optimization of land suitability. Results indicated that for cashew at very suitable class (S1) was 7,234.53 ha (37 %), S2 (suitable enough class) was 7,815.40 ha (40 %), S3 (suitable rather class) was2,918.6 ha (15 %) and N (inappropriate class) was 1,587.44 ha (8 %). Vanilla crop at very suitable class (S1) was2,126.14 ha (11 %), S2 (suitable enough class) was 8,965.10 (46 %), S3 (suitable rather class) was 1,333.86 ha (7%) and N (inappropriate class) was 7,130.88 ha (36 %). And coffee var. robusta crop at very suitable class (S1) was2,368.60 ha (12 %), S2 (suitable enough class) was 8,722.63 ha (45 %), S3 (suitable rather class) was 8,272.92 ha (42%) and N (inappropriate class) was 191 ha (1 %). From optimization process that was obtained 12 out of 13 land units with the optimum area gave the total benefit (Z max) of Rp. 55.9 billion at the fifth year production. This area consists of 6,749.28 ha (57.7 %) for crop cashew for class suitability of S1, S2, and S3; for coffee var. robusta crop of 4,932.74 ha (42.2 %) for class suitability of S1, S2, and S3, and for vanilla crop of 9.53 ha (0.1 %) for class suitability of S3.ABSTRAKPenelitian ini bertujuan untuk mengkaji kesesuaian lahan untuk pengembangan tanaman jambu mete, panili dan kopi robusta serta mengoptimalkannya untuk mendapatkan keuntungan yang maksimum. Pendekatan yang digunakan da lam mengkaji kesesuaian lahan adalah menggunakan software ArcGIS dengan mengoverlaikan peta ketinggian, peta kelerengan, peta jenis tanah, peta tekstur tanah, peta kedalaman tanah, peta drainase dan peta temperatur udara serta peta situasi sesuai dengan persyaratan lahan untuk tanaman jambu mete, panili dan kopi robusta guna mendapatkan peta kelas kesesuaian lahannya. Setelah diperoleh peta kesesuaian lahan maka dilakukan optimasi dengan menggu nakan software linear programming POMwin untuk mendapatkan peta kelas kesesuaian lahan yang optimum dengan keuntungan yang maksimum. Hasil kesesuaian lahan tanaman perkebunan diperoleh untuk jambu mete pada kelas kesesusaian S1 (sangat sesuai) seluas 7.234,53 ha (37 %), S2 (cukup sesuai) seluas 7.815,40 ha (40 %), S3 (agak se suai) seluas 2.918,62 ha (15 %) dan N (tidak sesuai) seluas 1.587,44 ha (8 %). Tanaman panili S1 seluas 2.126,14 ha (11 %), S2 seluas 8.965,10 ha (46 %), S3 seluas 1.333,86 ha (7 %) dan N seluas 7.130,88 ha (36 %). Serta tanaman kopi robusta S1 seluas 2.368,60 ha (12 %), S2 seluas 8.722,63 ha (45 %), S3 seluas 8.272,92 ha (42 %) dan N seluas191 ha (1 %). Dari hasil optimasi diperoleh 12 dari 13 satuan unit lahan yang ada dengan luas optimum 11.691,56 ha (60 %) dapat memberikan keuntungan maksimum (total Z maks) sebesar Rp 55,9 miliyar pada produksi tahun ke- 5 yang terdiri dari 6.749,28 ha (57,7 %) untuk tanaman jambu mete pada kelas kesesuaian S1, S2, dan S3, tanaman kopi robusta sebesar 4.932,74 ha (42,2 %) pada kelas kesesuaian S1, S2 dan S3, dan tanaman panili sebesar 9,53 ha (0,1%) pada kelas kesesuaian lahan S3.